Sinergi Mahasiswa dan Masyarakat dalam Penguatan Nilai Keagamaan dan Solidaritas Sosial di Kelurahan 26 Ilir Kota Palembang - Febriana, Rina; Najib, M. Ihsan; Ammar, Baez Kholil; Agustina, Dian; Mafiro, Ana (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This article documents and analyzes the synergy between students from the 84th Recognition Community Service Program (KKN) group at Raden Fatah State Islamic University in Palembang and the community in 26 Ilir Village, Bukit Kecil Subdistrict, Palembang City. As a heterogeneous and densely populated urban area, Kelurahan 26 Ilir faces sociocultural challenges in the form of declining religious literacy among the younger generation and a fading spirit of mutual cooperation due to the tide of modernization and urban individualism. This community service program was designed as a strategic partner for the village government and residents to revitalize religious values and strengthen social structures through acts of solidarity and community empowerment. The method used in implementing this community service program is a qualitative descriptive approach. Students conducted in-depth observations and direct interactions over a 30-day period, from January 19 to February 19, 2026. Data was collected through participatory observation and in-depth discussions with village officials and community leaders to narratively describe the phenomena, processes, and outcomes of the activities. The results of the community service program demonstrated significant impacts across three main aspects: physical-infrastructure, education-mentality, and social interaction. Physically, the “Kampung Sayur” was revitalized by painting the entrance gate to strengthen the area’s visual identity, and updating population information banners at the village office to ensure data transparency. In the educational sector, the Quranic study guidance program (BTQ) at the Jamiatul Islam Mosque successfully increased students’ interest and proficiency in understanding Tajwid and memorizing short surahs. Additionally, anti-bullying education at SD Negeri 136 provided crucial insights into the value of tolerance for students in an urban environment. Increased community participation was evident in the collaborative cleanup of drainage channels and residents’ involvement in the Posyandu for stunting prevention through the promotion of the Free Nutritious Food (MBG) program. The success of this program was supported by the openness of the village officials and the positive response from religious leaders. However, there were obstacles in the form of time constraints for residentsb most of whom work during the day as well as a lack of facilities and resources such as copies of the Quran and Iqro’ books. As a sustainability effort, the students initiated an “Islamic Reading Corner” at the mosque to ensure religious literacy continues after the KKN period ends. In conclusion, this collaborative synergy has proven capable of reviving local wisdom and strengthening the social and spiritual resilience of the community amidst the dynamics of modern urban life.